Teoria marxiana e consciência de classe: para uma crítica das ideologias marxistas adstringidas - Henrique Leao Coelho (2018)
The text has, as theoretical platform, the Marxian theory. In its limits, it tries to approach the ideological inputs of the class consciousness, that had the philosophy and the Marxian science like regencial bases. It is limited to raising, discussing and analyzing passages and contributions by Georg Lukács and José Chasin, who demonstrate the astringency of some Marxist theories that served functionally as ideology, observing the consequences of this process for the recognition and response to the historical-social conflicts for the working class. It is in this sense that it has as its scope the critique of astringent Marxist ideologies. For this, we will also show the gnosiological limits of the effective bourgeois ideology, especially in its moment of decadence, just as we will espouse on the Marxian theory in its non-astringent bias, that is, preserving its "structure" and "internal logic"